2019
DOI: 10.1186/s13018-019-1178-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with pain in nonsurgically treated rotator cuff tears -A study with magnetic resonance imaging

Abstract: Background In rotator cuff tears, some cases become asymptomatic with nonsurgical treatment, others remain symptomatic. The purpose of this study was to identify factors associated with pain in nonsurgically treated rotator cuff tears using magnetic resonance imaging (MRI). Methods In total, 108 shoulders diagnosed with supraspinatus (SSP) tendon tears using MRI were nonsurgically treated, and MRI was repeated after more than a year. The patients were divided into pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The difference between the two groups may be due to two factors: (1) the local in ammatory reaction caused by the knot resulted in adhesions between the shoulder joint and the surrounding tissues and even scar tissue formation, which affected the mobility in anterior exion and internal rotation [13,28,29] and (2) the fact that the suture loop during internal rotation and anterior exion exacerbated the tension imbalance between the bursal and articular side of the tendon, altering the tension on both sides of the tendon, which may cause stiffness [26,30]. However, Sahin et al showed that there was no statistical difference in the range of motion between the knotted technique and the knotless technique at almost two years post-operation [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the two groups may be due to two factors: (1) the local in ammatory reaction caused by the knot resulted in adhesions between the shoulder joint and the surrounding tissues and even scar tissue formation, which affected the mobility in anterior exion and internal rotation [13,28,29] and (2) the fact that the suture loop during internal rotation and anterior exion exacerbated the tension imbalance between the bursal and articular side of the tendon, altering the tension on both sides of the tendon, which may cause stiffness [26,30]. However, Sahin et al showed that there was no statistical difference in the range of motion between the knotted technique and the knotless technique at almost two years post-operation [20].…”
Section: Discussionmentioning
confidence: 99%
“…The suture bridge knotted technique has often been used clinically to repair rotator cuff tears. This technique increases the tendon-to-bone contact area and pressure, reduces the gap in the tendon-to-bone healing area, prevents the in ltration of joint uid, and ultimately promotes tendon-to-bone healing [1,[13][14][15]. However, previous reports have suspected that this technique is associated with higher retear rates, especially type 2 retears at the tendon-to-bone junction, which means remnant cuff tissue remained at the insertion site in spite of retear [3,10,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 30 Although an STT, which used to be called a hidden lesion, was not regarded as a major clinical problem, 19 , 31 it has been reported that it is associated with approximately 30% of rotator cuff tears (RCTs). 5 In addition, Nakamura et al 23 reported that the pain of RCTs with an STT is difficult to improve. Therefore, when a surgeon diagnoses RCTs with an STT, it is important to include the assessment of the anterosuperior aspect tear.…”
mentioning
confidence: 99%